Analisis Ekologi Faktor Risiko Gizi Buruk pada Balita di Tingkat Kabupaten/Kota Provinsi Kalimantan Selatan - Desie Rahmawati; Irma Desylia Maharani; Andry Rachmadani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Malnutrition remains a public health challenge in Indonesia because it impacts growth and development, and increases the risk of child morbidity and mortality. The causes of malnutrition are multifactorial, including direct and indirect factors. This study aims to analyze the factors that influence the incidence of malnutrition in toddlers in South Kalimantan Province. This study is a secondary data analysis using data sources from the 2023 South Kalimantan Provincial Health Profile, with 13 districts/cities as analysis units. The dependent variable is the percentage of malnutrition in toddlers, while the independent variables include the percentage of low birth weight (LBW), exclusive breastfeeding, and pneumonia. Data analysis was performed using multiple linear regression with the enter and backward methods. The results showed that only the variable of exclusive breastfeeding had a significant effect on the incidence of malnutrition (p <0.05), with a negative coefficient indicating that increasing the coverage of exclusive breastfeeding can reduce the incidence of malnutrition. Meanwhile, the variables of low birth weight (LBW) and pneumonia did not show a significant effect. The conclusion of this study is that exclusive breastfeeding is a factor that can reduce the risk of malnutrition in toddlers, so mothers are advised to exclusively breastfeed without additional food or drink until the baby is six months old to ensure optimal nutritional needs are met.